Teaching Effective Interpreters'communication Skills in Multimedia Classrooms - Tymchenko, I. I.; Badan, A. A.; Nedainova, I. V. (Таврійський національний університет імені В. І. Вернадського, 2020)
The development of new approaches to introducing communication exercises and activities imitating real life situations remains an urgent task for ESL teachers. This study examines the development of university students’ professionally significant communication skills during their classes of English taught in multimedia-based classrooms. The research conducted in groups of undergraduate students, who major in translation and interpreting, identified a set of the most valuable communication skills which require special attention of the novice interpreters. The necessity to focus on the development of these particular skills determined the methodology of teaching and the sequence of a year-long research, which 1) identified seven professionally significant communication skills that influence the efficiency of interpreters’ communication in working environment; 2) proved the advantages of teaching these skills to undergraduate students mainly in multimedia-based classrooms; 3) developed a convenient way to measure and assess the students’ individual progress in development of the seven professionally significant skills of communication, and 4) revealed ways to improve the technology of teaching by developing a set of exercises to be practiced in multimedia-based classrooms in order to imitate situations of working communication and interpreting. Introduction of the exercises in the teaching process has demonstrated appreciable improvement in students’ communication performances. Methodological recommendations for the teachers, who will be introducing the set of exercises in multimedia classrooms, were developed to ensure maximum efficiency of its applications.

У цьому дослідженні вивчається розвиток професійно значущих навичок спілкування студентів університету під час занять англійською мовою, що викладаються в мультимедійних аудиторіях. Дослідження, проведене в групах студентів бакалаврату, профілюючою дисципліною яких є усний та письмовий переклад, визначило набір найцінніших комунікативних навичок, які потребують особливої уваги початківців-перекладачів. Необхідність зосередження уваги на розвитку цих конкретних навичок зумовило методологію викладання та послідовність багаторічного дослідження, яке: 1) визначило 7 професійно значущих комунікативних навичок, що впливають на ефективність спілкування перекладачів у робочому середовищі; 2) довело переваги викладання цих навичок студентам саме в мультимедійних аудиторіях; 3) привело до розробки зручного способу розуміння та оцінки індивідуального прогресу студентів у вдо сконаленні 7 професійно значущих комунікативних навичок; 4) розкрило шляхи вдосконалення технології навчання шляхом розробки комплексу вправ, що відпрацьовуються саме в мультимедійній аудиторії з метою відтворення ситуацій робочого спілкування та перекладу. Впровадження цих вправ у навчальний процес показало помітне покращення у спілкуванні студентів. Для забезпечення максимальної ефективності застосування таких завдань були розроблені мето дичні рекомендації, якими можуть скористатися викладачі, що впроваджують комплекс цих вправ у мультимедійних аудиторіях.
Навчання ефективній комунікації перекладачів у мультимедійному класі
Keywords: multimedia-based classroom; interpreters’ communication skills; professionally significant skills; effective communication skills; imitation exercises; мультимедійна аудиторія; комунікативні навички перекладачів; професійно значущі навички; ефективні навички спілкування; імітаційні вправи